OC-001 SINGLE-STAGED ABDOMINAL WALL RECONSTRUCTION IN CONJUNCTION WITH ENTEROCUTANEOUS FISTULA REPAIR WITH AND WITHOUT ACELLULAR DERMAL MATRICES: A SINGLE CENTRE OBSERVATIONAL COMPARISON OF SHORT-TERM OUTCOMES. (13th October 2022) - Hodgkinson, J; Al-Kizwini, E; Leo, C A; Maeda, Y; Constantinides, J; Mehta, A; Warusavitarne, J; Vaizey, C
Abstract: Aim: Single-staged abdominal wall reconstruction (AWR) with simultaneous enterocutaneous fistula (ECF) repair is safe. This study aims to evaluate short-term outcomes from AWR with ECF repair and compare short-term outcomes between two commonly used acellular dermal matrices (ADM) as well as suture repair alone, with focus on ECF recurrence. Methods: Data were collected between 2011 and 2019 from a prospectively maintained operative database. A retrospective case-note review identifed patient demographics and post-operative outcomes. Kruskal-Wallis test was used for categorical variables and one-way ANOVA for continuous variables to evaluate between groups. Results: One hundred and fifteen cases were performed in the study period: 70 primary suture repair, 28 Surgimend and 17 Strattice. Fifty-eight patients (50.4%) were female with a mean age of 55.3 years (SD 13.9), BMI of 26.9 (SD 5.18) and 75 (65.2%) had intestinal failure. Median length of stay was 25 days (range 7–176). Overall, fistula recurrence rate was 10.4% (12 cases). Of these, 9 (12.8%) occurred in the suture repair group, 2 (11.8%) where a Strattice mesh was used and 1 (3.6%) where a Surgimend mesh was used (p=0.54). Forty-six patients (40%) had a Clavien Dindo complication of >3 and 73 patients (53.2%) had an SSI. Mortality was low at 2.8%. Conclusion: Single-staged AWR in conjunction with ECF repair remains a complex but safe undertaking. Initial experience suggests Surgimend is safe to use in the context of single-staged AWR and ECF recurrence rates are lower than with a comparable ADM with similar short-term outcomes.